Analisis abnormal returns dan trading volume activities - Kartika, Rayna; Firdaus (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Information contained in the capital market is the basis for investors in making decisions. This article is to investigate how much abnormal return (AR) and trading volume activities (TVA) are in the Indonesian capital market before and after the announcement of the new normal transition. The reaction of the capital market is important for investors in making decisions, so that investors know when to hold and buy shares with more precise estimates. When the Corona pandemic hit Indonesia, the world capital market was no exception in Indonesia, experiencing a slump. This is indicated by the stock price continuing to fall through the lower limit. For this reason, with the new normal transition, it is hoped that economic activity will be revived. So researchers are interested in knowing more about stock price movements before and after the new normal transition is announced and testing abnormal returns and trading volume activities on the LQ45 index. By conducting research on abnormal returns and trading volume activities in the capital market, information about stock prices can be more accurate so that it is more relevant in making decisions by investors.